(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Cervical bacterial infection is one of the main causes of Preterm Premature Rupture of Membranes (PPROM). The aim of this study was to identify the possible relationship with cervicovaginal bacterial infection in pregnant woman with preterm premature rupture of membrane. Materials and methods: This cross sectional study was conducted in Department of Obstetrics and Gynaecology of Chittagong Medical College Hospital, Chattogram, Bangladesh from April 2021 to September 2021. A total of 50 pregnant women with preterm premature ruptures of the membrane (28-37 weeks) were included in this study. Using SPSS version 23, collected data were coded, modified, and classed before being input into the computer for statistical analysis. Results: Culture of maternal high vaginal swab was positive in 39(78.0%) patients, among them 18(46.2%) patients were gram positive. Escherichia coli 11 (28.2%) was the most frequently isolated bacterium from high vaginal swab cultures. Age, antenatal checkup, vulvovaginal itching, BMI and mode of delivery were significantly associated in patient with PPROM with high vaginal swab culture positive patients (p<0.001). Conclusion: Culture of high vaginal swab in patients with PPROM was found positive in most of cases. Age, antenatal check up, vulvo-vaginal itching & BMI were significantly associated in patient with PPROM with high vaginal swab culture positive reports. JCMCTA 2024 ; 35 (2) : 77-81